Development and research of energy-efficient helio-air collectors for drying agricultural products - Kotov, Boris; Kalinichenko, Roman; Spirin, Anatolii; Gudzenko, Natalia; Didyk, Andrii; Zamrii, Mykhailo (Technology audit and production reserves, 2024)
The object of study is the drying of agricultural plant products. Artificial heat drying of agricultural plant products (seeds, fruits, nuts, grain, etc.), as a traditional method of canning and preparation for storage and further processing, usually takes place in dryers of seasonal use. To reduce the consumption of traditional types of organic fuel, it is proposed to use a lightweight portable film solar collector to heat the drying agent in seasonal dryers. A mathematical description of thermal processes in a solar collector is given. To increase the efficiency (degree of air heating), devices are proposed – heat exchange intensifiers. Effective methods of increasing the thermal power of the solar collector based on the use of ring and spiral turbolyzers of the coolant flow and sectional multi-pipe (multi-element) absorber have been theoretically substantiated, experimentally confirmed. The use of these structural elements of the solar collector will increase the thermal performance per unit area of the solar radiation absorber, which will increase the heating of the blunt carrier with 26 °С before 32 °C for tube absorbers and up to 36 °C for sectional absorbers. Maximum specific power of the solar collector with an area 240 m2 – 0.2 kW/m2 with a specific flow rate of the coolant of 23 m3/h·m2. For systems of active ventilation of seed material with specific air flow rates up to 100 m3/h·m2, it is possible to heat the atmospheric air up to 10 °C, which ensures round-the-clock drying of the product. A simplified mathematical model is formulated to intensify parameters according to the data of experiments. The heat transfer coefficients from the film absorber of solar energy to the heated air are determined. The results of the experimental determination of the thermal characteristics of the solar collector and its energy efficiency are presented. As the calculations showed, a further increase in the performance of the tubular solar collector is possible with an increase in the flow rate in the film absorber, which can be realized by reducing the diameter of the pipeline.